Tinjauan Kewajiban Dan Perlindungan Hukum Oleh Penyelenggara Platform Equity Crowdfunding Dalam Aplikasi LandX - Astrid Athina Indradewi; Carissa Amanda Siswanto; Jeffrey Hadi Soejono; Leonardo Caesar Haryono; Meyfa Angelita Elisabeth Mangkang (Ajudikasi : Jurnal Ilmu Hukum, 2022)
The presence of internet technology has provided many benefits and conveniences in human life. Technological advancements in the financial sector are also inevitable. One of the digital financial innovations in the financial services sector is crowdfunding. Equity crowdfunding is an activity to raise funds from the public using the internet as the media. Equity Crowdfunding or Information Technology-Based Crowdfunding Service has been regulated in POJK Number 57/POJK.04/2020 concerning Crowdfunding Services Through Information Technology-Based Stock Offerings. This mechanism provides opportunities and alternatives for entrepreneurs to obtain funding for their businesses. One of the providers of equity crowdfunding platforms in Indonesia is PT. Numex Technology Indonesia is a legal entity because it has fulfilled the requirements of POJK Number 57/POJK.04/2020 and registered with the Ministry of Communication and Information through the LandX application as well as is licensed and supervised by OJK and the Ministry of Communication and Information with the list number 001199.01/DJAI.PSE/07/2021. Through the LandX application, the financier and the property developer can meet in civil legal relations to buy and sell shares. When it can be proved that the organizer violated the financier's rights, then the organizer can also be liable based on default or tort law as stipulated in the Indonesian Civil Code. The high enthusiasm of Indonesian citizens for investment supported by the ongoing national and global economic recovery must inevitably be supported by protection for the risks that may arise. This research aims to analyze the mechanism of use, obligations, and legal protections by equity crowdfunding platform providers in LandX applications. This research uses normative juridical methods with a statutory approach and a conceptual approach.